2019
DOI: 10.1155/2019/5120581
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Mesoscale Network Structures

Abstract: When facing the problem of reconstructing complex mesoscale network structures, it is generally believed that models encoding the nodes organization into modules must be employed. The present paper focuses on two block structures that characterize the empirical mesoscale organization of many real-world networks, i.e. the bow-tie and the core-periphery ones, with the aim of quantifying the minimal amount of topological information that needs to be enforced in order to reproduce the topological details of the fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 34 publications
6
22
0
Order By: Relevance
“…several African nations, throughout our dataset). Notice that core size increases with time: apparently, thus, the system becomes increasingly integrated, confirming a result found in [17], where it was shown that the size of the WTW strongly connected component increases with time as well. a more refined criterion to judge the goodness of a fit is employed: solutions like the one of adopting criteria like the Akaike Information Criterion et similia have been proposed [29].…”
Section: Discussionsupporting
confidence: 85%
“…several African nations, throughout our dataset). Notice that core size increases with time: apparently, thus, the system becomes increasingly integrated, confirming a result found in [17], where it was shown that the size of the WTW strongly connected component increases with time as well. a more refined criterion to judge the goodness of a fit is employed: solutions like the one of adopting criteria like the Akaike Information Criterion et similia have been proposed [29].…”
Section: Discussionsupporting
confidence: 85%
“…An arrow in the opposite direction means that u is retweeting t . To filter out the random noise from this network, we make use of the directed version of the BiCM, i.e., the Bipartite Directed Configuration Model ( BiDCM [ 46 ]), described in Sect. 6.2 .…”
Section: Resultsmentioning
confidence: 99%
“…In the previous section, we obtained the political affiliation of verified users by projecting the information in the bipartite network describing the interactions between verified and unverified users. Now, we will apply the entropy-based null model, in its directed variant-Bipartite Directed Configuration Model (BiDCM)-proposed by van Lidth de Jeude et al 48 , to filter the total exchange of content in our dataset, after discounting the information regarding the activity of users and the virality of messages, as in ref. 32 .…”
Section: Resultsmentioning
confidence: 99%
“…approach is similar to the one adopted for the extraction of the users political affiliation. The difference consists in (1) substituting the BiCM with its analogous directed version, the BiDCM (proposed by van Lidth de Jeude et al 48 ) and in (2) considering layers of different kind. While in the previous section layers represent verified and unverified users, here they represent tweets on one layer and users (both verified and unverified) on the other.…”
Section: Methodsmentioning
confidence: 99%